The role of amino acid metabolism in inflammatory bowel disease and other inflammatory diseases - Zheng, Xiaowen; Zhu, Yi; Zhao, Zihan; Chu, Ying; Yang, Wenjing (Frontiers in Immunology, 2023)
Inflammation is a characteristic symptom of the occurrence and development of many diseases, which is mainly characterized by the infiltration of inflammatory cells such as macrophages and granulocytes, and the increased release of proinflammatory factors. Subsequently, macrophage differentiates and T cells and other regulated factors exhibit anti-inflammatory function, releasing pro- and anti-inflammatory factors to maintain homeostasis. Although reports define various degrees of metabolic disorders in both the inflamed and non-inflamed parts of inflammatory diseases, little is known about the changes in amino acid metabolism in such conditions. This review aims to summarize amino acid changes and mechanisms involved in the progression of inflammatory bowel disease (IBD) and other inflammatory diseases. Since mesenchymal stem cells (MSCs) and their derived exosomes (MSC-EXO) have been found to show promising effects in the treatment of IBD and other inflammatory diseases,their potential in the modulation of amino acid metabolism in the treatment of inflammation is also discussed.